Authority Of Special Detachment 88 Of The Indonesian National Police In The Prevention Of Terrorist Crimes In The Jurisdiction Of The Bali Provincial Police (Polda Bali) - Suadnyana, Made; Wiratny, Ni Ketut; Suryana, Kadek Dedy (Pelopor Publikasi Akademika, 2025)
In enforcing the law on terrorism crimes, Densus 88 has broad authority including , arrest, investigation, and prosecution of suspected terrorists. This authority is regulated in Article 25 of Law Number 15 of 2003, which has been amended by Law Number 5 of 2018, and Law Number 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism. Investigation, prosecution, and trial of terrorism crimes must be carried out in accordance with applicable legal procedures, unless there are other provisions in government regulations that replace this law. The problem is how is the authority of the Special Detachment 88 against perpetrators of terrorism in the Bali Regional Police, and how are the efforts to prevent terrorism crimes in the Bali Regional Police? (Polda) Special Detachment 88 has the authority to detain suspects for a maximum of months for the purposes of criminal investigation and prosecution, with the possibility of an extension of up to 7 times 24 hours in the arrest of terrorism, in accordance with Article 28. The efforts of the Special Detachment (Densus) 88 Police in Preventing Terrorism Crimes include preventive measures; in the form of socialization and education on terrorism to the community, coaching and mentoring for prisoners and former prisoners of terrorism in the social and economic fields, collaborating with various stakeholders such as universities and schools, the Social Service, and others. Repressive actions target arrests and prosecutions as well as trial trials for perpetrators of terrorism based on sufficient evidence.